The doctoral research abstracts. Vol:10 2016 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduate Studies (Institute of Graduate Studies, 2016)
Foreword: Congratulations to Institute of Graduate Studies on the continuous efforts to publish the 10th issue of the Doctoral Research Abstracts which showcases the research carried out in the various disciplines range from science and technology, business and administration to social science and humanities. This issue captures the novelty of research contributed by seventy (70) PhD graduands receiving their scrolls in the UiTM’s 85th Convocation. As of October 2016, this year UiTM has produced 138 PhD graduates soaring from125 in the previous year (2015). It shows that UiTM is in the positive direction to achive the total of 1200 PhD graduates in 2020. To the 70 doctorates, I would like it to be known that you have most certainly done UiTM proud by journeying through the scholarly world with its endless challenges and obstacles, and by persevering right till the very end. This convocation should not be regarded as the end of your highest scholarly achievement and contribution to the body of knowledge but rather as the beginning of embarking into more innovative research from knowledge gained during this academic journey, for the community and country. This year marks UiTM’s 60th Anniversary and we have been producing many good quality graduates that have a major impact on the socio-economic development of the country and the bumiputeras. As alumni of UiTM, we hold you dear to our hearts. We sincerely wish you all the best and may the Almighty guide you to a path of excellence and success. As you leave the university as alumni we hope a new relationship will be fostered between you and the faculty in soaring UiTM to greater heights. “UiTM Sentiasa di Hati Ku” / Prof Emeritus Dato’ Dr Hassan Said Vice Chancellor Universiti Teknologi MARA